Integrin alpha 2 is associated with tumor progression and postoperative recurrence in non-small cell lung cancer. (23rd September 2022) - Matsumoto, Yoko; Kage, Hidenori; Morota, Mizuki; Zokumasu, Koichi; Ando, Takahiro; Maemura, Keita; Watanabe, Kousuke; Kawakami, Masanori; Hinata, Munetoshi; Ushiku, Tetsuo; Nakajima, Jun; Nagase, Takahide
Abstract: Background: Integrins are transmembrane proteins that mediate cell adhesion to extracellular matrix. Whereas expression of integrin alpha 2 is associated with motility, invasiveness and cellular differentiation in various tumors, the role of integrin alpha 2 in lung cancer has not been studied in detail. The aim of this study was to determine whether and how aberrant integrin alpha 2 expression in non-small cell lung cancer leads to different outcomes. Methods: We measured expression of integrin alpha 2 by quantitative polymerase chain reaction in 100 samples collected from non-small cell lung cancer patients who had undergone surgical resection. We assigned patients to high and low expression groups and analyzed survival. Cellular morphology, adhesion, proliferation, migration and invasion were examined in human lung cancer cell lines. Results: Among 100 cases, 41 were female, with a median age of 71 years. High expression of integrin alpha 2 in non-small cell lung cancer was associated with lower recurrence-free survival ( P  = 0.004). Overexpression of integrin alpha 2 in cell lines had no effect on cell proliferation or invasion but resulted in increased cell size (1416 μm 2 versus 470 μm 2 in H522 cells, P  < 0.001; 1822 μm 2 versus 1029 μm 2 in H661 cells, P  = 0.02), adhesion ( P  < 0.001 in H522 and H661 cells) and migration (gap area filled was 71% versus 36% in H522 cells, P  < 0.001; 57% versus 26% in H661 cells, P  = 0.001). These changes were suppressed by E7820, an inhibitor of integrin alpha 2. Conclusions: Integrin alpha 2 may play a significant role in lung cancer adhesion and migration, and may lead to a higher risk of recurrence. Abstract : High expression of integrin alpha 2 in non-small cell lung cancer was associated with postoperative recurrence. Integrin alpha 2 plays a significant role in cancer adhesion and migration, which may lead to a higher risk of recurrence.